A Holistic Study on the Effect of Annealing Temperature and Time on CH3NH3PbI3-Based Perovskite Solar Cell Characteristics - Ali Akhavan Kazemi, Mohammad; Jamali, Arash; Sauvage, Frédéric (Frontiers in Energy Research, 2021)
The time and annealing temperature for the film crystallization in perovskite solar cells (PSCs) is critical and is at the stake of device optimization. It governs the crystallization process, the film’s morphorlogy and texture and the level of non-radiative defects, which in whole control the power conversion efficiency (PCE). However, deciphering each of these parameters in the device cell characteristics remains not totally clear. In this work, we led a holistic study considering temperature and time for the MAPbI3 crystallization as a free parameter to study how the latter is impacting on the film’s characteristics and how the device figure of merit is affected. The results suggest that the crystallinity level of the grains plays an important role in the photo-current value whereas the morphology and PbI2 impurities resulting from the onset of thermal decomposition of MAPbI3 penalizes the cell photovoltage and the fill factor values. Based on this study, it is highlighted that flash high temperature annealing is beneficial to limit out-of-plane substrate grain boundaries, resulting in a device exhibiting 18.8% power conversion efficiency compared to 18.0% when more standard post-annealing procedure is employed.